0.15-0.01(x+1)=0.03(2-x)

Simple and best practice solution for 0.15-0.01(x+1)=0.03(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.15-0.01(x+1)=0.03(2-x) equation:



0.15-0.01(x+1)=0.03(2-x)
We move all terms to the left:
0.15-0.01(x+1)-(0.03(2-x))=0
We add all the numbers together, and all the variables
-0.01(x+1)-(0.03(-1x+2))+0.15=0
We multiply parentheses
-0.01x-(0.03(-1x+2))-0.01+0.15=0
We calculate terms in parentheses: -(0.03(-1x+2)), so:
0.03(-1x+2)
We multiply parentheses
-0.03x+0.06
Back to the equation:
-(-0.03x+0.06)
We add all the numbers together, and all the variables
-0.01x-(-0.03x+0.06)+0.14=0
We get rid of parentheses
-0.01x+0.03x-0.06+0.14=0
We add all the numbers together, and all the variables
0.02x+0.08=0
We move all terms containing x to the left, all other terms to the right
0.02x=-0.08
x=-0.08/0.02
x=-4

See similar equations:

| 3xX=44 | | 5h–6=–8+7h | | 11x+5=x+9 | | 9.k+3.5+4.8k=-46.2 | | -36+14x=12+x30 | | 21=3x23 | | 12+r=29 | | 2y+4÷5=30 | | 5=d/11 | | 2.3+10m=6.49 | | Y=23x-6 | | 12/3=m-4/5 | | 32=5d+12 | | x+10=2(2x-1) | | 45+63+90=x | | 56=k=42 | | 1.4=w/6 | | 8x+2(-4x-23)=-46 | | (8x-4)+60=90 | | 45+63+90+x=180 | | 5.5=t/3 | | -3.3+r=5.1 | | 123=m-45 | | 7q+6=68 | | (x+3)^2=x^2–3(1–x) | | 10x+7=36 | | 5x-6-4x=4 | | -57=9-4x | | 5(b+5)=100 | | v/4-4=-3 | | y-45=70 | | q+2q+2q+22+3(2q+22)=2134 |

Equations solver categories